Franco-Scottish relations in the first third of the XV century - Oleg Igorevich Nuzhdin (Античная древность и средние века, 2019)
The article tells about the development of the bilateral relations between Scotland and France at the beginning of the XV century. One of the most complex and complicated unions that has even been developed. The 20-s of the XV century was the crucial moment at the Hundred Year’s war in general and at the French-Scottish relations in particular. The whole article reveals the complexity and importance of the issue and defines the situation at the great arena of the relations between England, France and Scotland.